(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Budanova L. G. The content, tools and structure of the diagnostic of future pharmacists’ training level in higher educational institutions of Eastern European countries. The article deals with the content, tools and structure of the diagnostic of future pharmacists’ training level in higher educational institutions of Eastern European countries according to their training level, distribution of educational disciplines on training cycles. Knowledge and practical skills that are necessary for the diagnostics of specialist training for pharmaceutical industry have been analyzed. The need for deeper study of foreign higher pharmaceutical education has caused an urgent requirement of time to achieve a higher level of global pharmaceutical sector development. So, it becomes important to analyze the positive experience in reforming foreign higher pharmaceutical education. The experience of Eastern European countries is close to Ukraine. Eastern European and Ukrainian models of future pharmacists’ professional training have much in common and distinguishing features caused by historically formed traditions and national features, socio-economic and spiritual development of states, conceptual foundations of educational policy. So, the conducted research has found out that in the educational process the integration of humanitarian and professional component in the training of future specialist for pharmaceutical industry; individualization and differentiation of education; professional orientation in teaching humanitarian, socio-economic and natural sciences haven’t been implemented.